Worsening calcification propensity precedes all-cause and cardiovascular mortality in haemodialyzed patients. Issue 1 (December 2017) - Lorenz, Georg; Steubl, Dominik; Kemmner, Stephan; Pasch, Andreas; Koch-Sembdner, Wilhelm; Pham, Dang; Haller, Bernhard; Bachmann, Quirin; Mayer, Christopher; Wassertheurer, Siegfried; Angermann, Susanne; Lech, Maciej; et al.
Abstract A novelin-vitro test (T50 -test) assessesex-vivo serum calcification propensity which predicts mortality in HD patients. The association of longitudinal changes of T50 with all-cause and cardiovascular mortality has not been investigated. We assessed T50 in paired sera collected at baseline and at 24 months in 188 prevalent European HD patients from the ISAR cohort, most of whom were Caucasians. Patients were followed for another 19 [interquartile range: 11–37] months. Serum T50 exhibited a significant decline between baseline and 24 months (246 ± 64 to 190 ± 68 minutes; p < 0.001). With serum Δ-phosphate showing the strongest independent association with declining T50 (r = −0.39; p < 0.001) in multivariable linear regression. The rate of decline of T50 over 24 months was a significant predictor of all-cause (HR = 1.51 per 1SD decline, 95% CI: 1.04 to 2.2; p = 0.03) and cardiovascular mortality (HR = 2.15; 95% CI: 1.15 to 3.97; p = 0.02) in Kaplan Meier and multivariable Cox-regression analysis, while cross-sectional T50 at inclusion and 24 months were not. Worsening serum calcification propensity was an independent predictor of mortality in this small cohort of prevalent HD patients. Prospective larger scaled studies are needed to assess the value of calcification propensity as a longitudinal parameter for risk stratification and monitoring of therapeutic interventions.